CONSIDERATION OF AKHLAKUL KARIMAH USING PANCASILA STUDENT PROFILES - Zakiyah; Nikem Kurnia Ningsih; Uswah; Maya Lestari; Hany Arianty (RADJA PUBLIKA, 2025)
The consideration method is a learning method that develops children's personalities into creative people with high morality. Starting when entering school age, because children are more required to have good religious values and morals when receiving education in schools, these roles include aspects of faith, worship and morals. While in the student environment there are still many children who say bad things, often fight and lack knowledge about worship. This study aims to improve the religious values and morals of early childhood and the obstacles faced by teachers in improving children's character using the independent curriculum in implementing the Pancasila student profile. This study uses a descriptive qualitative method with a type of field research. Data collection used through observation, interviews and documentation. The informants interviewed were 5 parents and 3 teachers as well as documentation from learning activities. From the results of the study based on the interview, the role of parents and teachers in improving religious values and morals in children based on the Pancasila student profile in the independent curriculum, among others, parents are very satisfied and grateful for the changes in their children after the teacher applies religious values and morals to the Pancasila student profile, as well as teachers who say that the class becomes conducive and children's bad words are no longer there, the character of children at school already reflects a very good Pancasila profile in accordance with religious values and morals with the Consideration of Morals method Using the Pancasila Student Profile at the Age of 4-5 Years at Aisyiyah Bustanul Athfal Panongan 1 Kindergarten has succeeded in improving its students to have morals.